The Role of Oxidative Stress in Atopic Dermatitis and Chronic Urticaria - Sabina Galiniak; Mateusz Mołoń; Marek Biesiadecki; Agnieszka Bożek; Marta Rachel (MDPI AG, 2022)
Atopic dermatitis (AD) and chronic urticaria (CU) are common skin diseases with an increasing prevalence and pathogenesis that are not fully understood. Emerging evidence suggests that oxidative stress plays a role in AD and CU. The aim of the single-center cross-sectional study was to compare markers of oxidative stress in 21 patients with AD, and 19 CU patients. The products of protein oxidation, total antioxidant capacity (TAC), and markers of lipid peroxidation were estimated in the serum. AD patients had a higher level of advanced protein oxidation products and a lower level of thiol groups than healthy participants. However, CU patients had statistically higher levels of AOPP and 3-nitrotyrosine than healthy subjects. The level of thiol groups and serum TAC decreased significantly in patients with CU. There was no difference in serum concentration of lipid peroxidation products, Amadori products, ratio of reduced to oxidized glutathione, and ability of albumin to binding cobalt between AD or CU patients compared to healthy subjects. We found a moderate positive significant correlation between AOPP and age in patients with AD. In patients with CU, TAC was negatively correlated with age. These results may shed light on the etiopathogenesis of AD or CU, and confirm an oxidative burden in these patients. Furthermore, our study could be useful in developing new therapeutic methods that include using antioxidants in dermatological diseases.